U.S Democracy Campaign during The Civil War in Libya - Putri Kartika, Adelia Alviani (Jurnal Diplomasi Pertahanan, 2021)
The NATO intervention in Libya was one of the most contentious conflict in 2011. The permission given by the UNSC for NATO to intervene in Libya led to a debate that said intervention carried out in Libya was not based on the humanitarian objectives but for US national interest. This situation is strengthened by several NATO activities that show their involvement is for the US interest. Some of the US interest are protecting their territorial sovereignty from terrorism, oil interest and democracy campaign or ideology. Ideology is counted as their long-range or important interest. Previous studies have explained the other US interest in Libya such as the oil interest and terrorism. However, there are not many studies that precisely portray the importance of liberalism in this operation. Therefore, this research is questioning on the importance of democracy campaign during operation by NATO for the US. The main argument in this study is that US did not only launch the operation for humanitarian reason but for its own interest and that democracy liberal ideology interest hold the same importance as the other interest of US.